Animal biotechnology research and development initiatives in Malaysia - Ideris, Aini (Universiti Putra Malaysia Press, 2004)
The poultry and pig industries are highly dependent on imported feeds with negligible production of feed crops, and under-utilisation of agro-industrial by-products. The slow growth of the ruminant subsector may be because of the low base population of cattle, buffaloes, sheep and goats for rapid multiplication, limiting the ability for intensive selection for genetic improvement. Artificial insemination technology has not been fully utilized to multiply superior stock and produce crossbred animals because of poor conception rates. Fish production can be intensified by good management over different functions and variables of the cultivated organisms, the stock and their environment. The concept of farming systems reflects the existence of relationships between resource variables; only certain systems are ecologically, biologically and technically viable. Malaysian scientists have carried out research on various aspects of biotechnology as means of enhancing the economic production of livestock and fish. These are now a strong network among researchers in the universities and research institutions. Multidisciplinary and inter-institutional research is encouraged. Recent advances in biotechnology are applied in order to develop rapid and cost effective diagnostic reagents, vaccines and other biologics, to improve genetic resources for ruminant and fish production, and to improve local feed resources. Animal models are also used for the study of human health.